2017
DOI: 10.1515/rjim-2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

Importance of arterial stiffness in predicting cardiovascular events

Abstract: Introduction. Cardiovascular events represent an important cause of morbidity and mortality in the entire population. Arterial stiffness is currently considered one of the most important risk factors for the development of cardiovascular events. The gold-standard for evaluating arterial stiffness is pulse wave velocity (PWV). Recent studies have demonstrated that PWV is an independent risk factor regarding the development of cardiovascular events, especially in certain categories of patients.Material and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Arterial stiffness impairs relaxation of blood vessels and contributes to an augmentation of the blood pressure. Increased AS has been shown to correlate with cardiovascular morbidity and mortality [116,117]. Decreased vasodilatation in coronary arteries with established atherosclerosis induced vasoconstriction may result in reduced myocardial perfusion and myocardial ischemia [118].…”
Section: Vascular Dilatation and Blood Pressurementioning
confidence: 99%
“…Arterial stiffness impairs relaxation of blood vessels and contributes to an augmentation of the blood pressure. Increased AS has been shown to correlate with cardiovascular morbidity and mortality [116,117]. Decreased vasodilatation in coronary arteries with established atherosclerosis induced vasoconstriction may result in reduced myocardial perfusion and myocardial ischemia [118].…”
Section: Vascular Dilatation and Blood Pressurementioning
confidence: 99%
“…Aging is associated with a progressive increase in vascular stiffness and PP 2 . High PP has been attributed to elastic fiber degeneration and aortic dilation, which transfers the hemodynamic load to stiffer collagen 14 ; this condition is associated with an increased risk for cardiovascular disease and overall mortality 15 , 16 . Therefore, effective management of PP is very important to prevent cardiovascular disease and to ensure a healthy life in the elderly 6 , 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness is a process that results in deterioration of certain hemodynamic functions with reduced aortic compliance and elasticity due to the factors such as advanced age, HT, DM, HPL, smoking and renal failure [ 16 ]. In the previous studies, it was indicated that arterial stiffness was shown to be an independent predictor for cardiovascular mortality and all-cause deaths [ 9 , 15 , 20 , 22 , 28 ]. Development of aortic stiffness leads to an increase in central systolic blood pressure, a decrease in diastolic blood pressure and hence an increase in PP with multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“… PWV = ΔD/Δt PWV is now regarded as the gold standard for the measurement of aortic stiffness [ 26 , 27 ]. It was shown that the PWV calculated based on the measurements at the carotid and femoral arteries is an independent risk factor for cardiovascular mortality and morbidity [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation